ANALISIS KESALAHAN PENGGUNAAN TANDA BACA DALAM MENULIS TEKS PERSUASI SISWA KELAS VIII SMP NEGERI 3 SIDUA’ӦRI - Sari Hulu, Ratna (KOHESI : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research aims to describe the errors in punctuation usage in writing persuasive texts by eighth-grade students at SMP Negeri 3 Sidua’ӧri. The method used in this study is qualitative research with a descriptive approach. Based on the research results, it can be concluded that the analysis of punctuation errors in writing persuasive texts by eighth-grade students at SMP Negeri 3 Sidua’ӧri consists of three types: errors in the use of the period (.), comma (,), and exclamation mark (!). The types of punctuation errors most frequently made by the eighth-grade students are related to the use of periods, commas, and exclamation marks. Thus, the students' ability to use punctuation correctly in writing persuasive texts indicates a lack of understanding and mastery of proper punctuation usage, leading to numerous errors in their written work, as seen in the individual persuasive texts. Based on these findings, the researcher can provide several recommendations: (1) For teachers or prospective teachers, they can offer writing exercises to students, pay attention to the students' writing outcomes, frequently assign tasks, and remind students about the correct use of punctuation. (2) For students, this research can serve as a reference for achieving the basic competency indicators in writing. (3) For readers, this can act as a guideline and a source of knowledge to enhance understanding of punctuation usage errors.